An Investigation into the Acute and Subacute Toxicity of Extracts of Cassipourea flanaganii Stem Bark In Vivo - Nomakhosi Mpofana; John Kudakwashe Chipangura; Michael Paulse; Masande Yalo; Nceba Gqaleni; Celenkosini Thembelenkosini Nxumalo; Ncoza Cordelia Dlova; Ahmed A. Hussein; Neil R. Crouch (Plants, 2023)
The conventional use of medicinal plants is in part based on the widespread belief that plant crude extracts are non-toxic. In South Africa, traditional preparations of Cassipourea flanaganii used to treat hypermelanosis have accordingly been regarded by many as non-toxic. Whether that is so impacts on the potential of bark extracts to be developed as a commercial drug to treathypermelanosis, given their documented capacity to inhibit tyrosinase activity. Our study investigated the acute and subacute toxicity of the methanol extract of C. flanaganii bark in rats. Wistar rats were randomly assigned into different treatment groups. The rats received a daily oral gavage of crude extract for acute and subacute toxicity tests. Haematological, biomechanical, clinical and histopathology examinations were carried out to evaluate the possible toxicity of C. flanaganii. The results were subjected to the Student’s t-test and ANOVA. For both acute and subacute toxicity, there was no statistical difference between the groups. There were no clinical or behavioral signs of toxicity observed in the rats. No treatment-related gross pathology lesions and no histopathology were observed. The findings of this study demonstrate the absence of acute or subacute toxicity after oral treatment with C. flanaganii stem bark extracts in Wistar rats at the levels administered. Chemical profiling of the total extract using LC-MS tentatively identified eleven (11) compounds as the major chemical constituents.